Application of Morgenstern-Price Method in Reversion Analysis of the Loess Strength Parameters. Issue 1 (November 2020) - Lin, Xiaoyan; Zhang, Linfan; Yang, Ze; Li, Ping; Li, Tonglu
Abstract: It is difficult to obtain reliable shear strength parameters for the stability analysis and evaluation of high loess slopes. Hence, this paper determines 17 slopes with a height of 40-120 m based on the measured loess slopes in Jingbian-Ansai subregion of northern Shaanxi, China. The model is established using the finite element method, and the comprehensive shear strength parameters of different slope heights of the high slope in the study area are obtained by inversion using the Morgenstern-Price method. The results show that when the height of the slope increases, the cohesion c in the soil increases, and the internal friction angle φ decreases. According to the calculation results, a comprehensive inversion curve of strength parameters under the slope height of 40 to 120 m is drawn, which can directly evaluate the stability of the loess high slope, which improves the work efficiency and also provides reliable data support in the high side Slope geometry design.